Efficacy and safety of biosimilar CT-P13 compared with originator infliximab in patients with active Crohn's disease: an international, randomised, double-blind, phase 3 non-inferiority study. Issue 10182 (27th April 2019) - Ye, Byong Duk; Pesegova, Marina; Alexeeva, Olga; Osipenko, Marina; Lahat, Adi; Dorofeyev, Andriy; Fishman, Sigal; Levchenko, Olena; Cheon, Jae Hee; Scribano, Maria Lia; Mateescu, Radu-Bogdan; Lee, Kang-Moon; et al.
Summary: Background: The infliximab biosimilar CT-P13 was approved for use in Crohn's disease after clinical comparison with originator infliximab in ankylosing spondylitis and rheumatoid arthritis; however, concerns about such indication extrapolation have been expressed. This study investigated whether CT-P13 is non-inferior to infliximab in patients with Crohn's disease who were naive to biological therapy. Methods: In this randomised, multicentre, double-blind, phase 3 non-inferiority study, we enrolled patients with active Crohn's disease who had not responded to, or were intolerant to, non-biological treatments. Patients were randomly assigned (1:1:1:1) to receive CT-P13 then CT-P13, CT-P13 then infliximab, infliximab then infliximab, or infliximab then CT-P13, with switching occurring at week 30. Patients received 5 mg/kg CT-P13 or infliximab at weeks 0, 2, 6, and then every 8 weeks up to week 54. The primary endpoint was the proportion of patients with a decrease of 70 points or more in Crohn's Disease Activity Index (CDAI) from baseline to week 6. A non-inferiority margin of −20% was set (CT-P13 was non-inferior to infliximab if the lower limit of the two-sided 95% CI for the treatment difference was greater than −20). This trial is registered with ClinicalTrials.gov, number NCT02096861, and is completed. Findings: Between Aug 20, 2014, and Feb 15, 2017, 308 patients were assessed for eligibility, and 220 patients were enrolled: 111 were randomly assigned to initiate CT-P13 (56 to the CT-P13–CT-P13 group and 55 to the CT-P13–infliximab group) and 109 to initiate infliximab (54 to the infliximab–infliximab group and 55 to the infliximab–CT-P13 group). CDAI-70 response rates at week 6 were similar for CT-P13 (77 [69·4%, 95% CI 59·9 to 77·8] of 111) and infliximab (81 [74·3%, 95% CI 65·1 to 82·2] of 109; difference −4·9% [95% CI −16·9 to 7·3]), thereby establishing non-inferiority. Over the total study period, 147 (67%) patients experienced at least one treatment-emergent adverse event (36 [64%] in the CT-P13–CT-P13 group, 34 [62%] in the CT-P13–infliximab group, 37 [69%] in the infliximab–infliximab group, and 40 [73%] in the infliximab–CT-P13 group). Interpretation: This study showed non-inferiority of CT-P13 to infliximab in patients with active Crohn's disease. Biosimilar CT-P13 could be a new option for the treatment of active Crohn's disease. Funding: Celltrion, Pfizer.